The Serious Consequences of the Implementation of EU Policies regarding Biofuels - Dorobat, Leonard Magdalin; Turtureanu, Anca; Dobrescu, Codruta Mihaela (Journal of Danubian Studies and Research, 2024)
Biofuels are defined, according to the EU directive on renewable energy, as "liquid fuels for transport produced from biomass" and must meet certain sustainability criteria (European Commission, Biofuels). In 2021, the majority of biofuels consumed in the EU were mainly crops (mainly ethanol and biodiesel). On the other hand, after many analyses, it is reported that the efficiency of the use of biofuels in terms of reducing the greenhouse effect is greatly overestimated. Considering that the availability of biomass in the EU for the production of biofuels is quantitatively limited, then the argument of the European Commission regarding the contribution of the use of biofuels to the energy independence of the EU is also not true. Another problem is that the production of biofuels in the EU is expensive, labor costs, energy costs, environmental taxes, etc. make the price of biofuels produced in the EU high. Because of this policy, the high demand for biofuels in the EU (ethanol or biodiesel) led in other countries of the world to the intention to satisfy this need. As a result, in countries such as Brazil, Indonesia, the Philippines, Malaysia, etc., plants from which to produce biodiesel and ethanol began to be grown on an increasingly large scale, one of these plants being the oil palm. The consequences are serious. In many countries very large areas of forest have disappeared, to make way for the cultivation of plants for biofuels. Another serious aspect of the problem is the fact that many people arround the globe are already suffering from hunger or from the fact that they cannot afford minimally satisfying food. Changing the destination of many agricultural lands used for food production to be used for the production of biofuel leads to an impoverishment of food resources, which is unacceptable! Practically, the foolish policy of the European Commission regarding the environment has led to the export of negative social and environmental consequences to other countries. This is not ethical or moral. It is not acceptable to protect the environment in the EU, which is associated with a decrease in food availability, nor at the expense of the environment in other countries. Environmental protection, in this regard, is a global problem; fewer forests on a planetary level means less carbon dioxide absorbed and stored, resulting in a greater greenhouse effect. It is absurd to think that by using biofuels in the EU, you pollute less, practically somewhere, a country has deforested large areas, to produce this biofuel, and the effect is a decrease in the absorption of carbon dioxide and therefore an increase in the greenhouse effect. However, deforestation has multiple negative effects, such as landslides, erosion, the degradation of agricultural land adjacent to forests, the disappearance of springs, the disappearance of many species of living things, with tragic and irreversible consequences on the ecosystems and, implicitly, with serious economic consequences.